2015
DOI: 10.1063/1.4907580
|View full text |Cite
|
Sign up to set email alerts
|

Fast strain wave induced magnetization changes in long cobalt bars: Domain motion versus coherent rotation

Abstract: A high frequency (88 MHz) traveling strain wave on a piezoelectric substrate is shown to change the magnetization direction in 40 lm wide Co bars with an aspect ratio of 10 3 . The rapidly alternating strain wave rotates the magnetization away from the long axis into the short axis direction, via magnetoelastic coupling. Strain-induced magnetization changes have previously been demonstrated in ferroelectric/ferromagnetic heterostructures, with excellent fidelity between the ferromagnet and the ferroelectric do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The SAW could thus-in theory-affect both steps of the reversal. It has been argued, however [16], that the high frequencies of SAWs (>100 MHz) would not allow enough time for the relatively slow DW propagation (speeds of tens of ms −1 in GaMnAs [27])-unless particular geometries are used [17]so we focus on their effect on nucleation. The concavity of the magnetic aftereffect curves taken under SAW [inset of Fig.…”
Section: Fig 5 Kerr Microscopy Images (690 × 924 μMmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAW could thus-in theory-affect both steps of the reversal. It has been argued, however [16], that the high frequencies of SAWs (>100 MHz) would not allow enough time for the relatively slow DW propagation (speeds of tens of ms −1 in GaMnAs [27])-unless particular geometries are used [17]so we focus on their effect on nucleation. The concavity of the magnetic aftereffect curves taken under SAW [inset of Fig.…”
Section: Fig 5 Kerr Microscopy Images (690 × 924 μMmentioning
confidence: 99%
“…Relying on this coupling, recent work has predicted [12,13] and demonstrated experimentally [14] that acoustic waves can trigger resonant precessional switching. SAWs can moreover assist-nonresonantly-the coherent reversal of small structures [15,16], or in larger samples could trigger the nucleation or propagation of domain walls [13,17]. In that case, the lever is expected to be the dependency of the domain wall energy on the magnetoelastic constant.…”
mentioning
confidence: 99%
“…This has been made possible thanks to the huge sensitivity of the magnetic anisotropy to strain [14,15]. Strain waves like SAWs have been identified as a powerful tool for magnetization switching in magneto-strictive materials [16,17,18]. In GaMnAs it was recently demonstrated that magnetization precession can be resonantly driven by a SAW when both the magnon and phonon frequencies match [13], which is the first necessary step toward precessional switching [12].…”
Section: Introductionmentioning
confidence: 98%
“…For the latter two however [2][3][4][5][6][7], the necessity for biasing fields remains ubiquitous, whether spin-transfer, spin-orbit torques, or electric-field modulations of the anisotropy are at play. A recently developed alternative for magnetization switching is the use of acoustic waves [8][9][10][11][12][13][14][15]. The effective field generated by Rayleigh waves through inverse magnetostriction can switch magnetization efficiently in magnetostrictive thin films of both in-plane and out-of-plane anisotropies [14,15].…”
Section: Introductionmentioning
confidence: 99%